(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The formation of entrepreneurial culture in Ukraine is an extremely important element for countries whose economies are in the stage of development and transformation. The startup ecosystem is one of the determinants of the components of this complex process. Changes that have taken place over the last century confirm the fact of changes in the paradigm of entrepreneurship. During the last decade, most of the growth of the workforce was due to the successful implementation of startup projects. The purpose of the article is to show the peculiarities of the startup ecosystem in Ukraine. The largest number of Ukrainian startups that have attracted venture and angel funding in the field of creating online services and software. Startups the most are interested and financed by investors in the field of marketing, hardware, e-commerce and the mobile services market. Among the countries that invest the most in Ukrainian startup projects in 2019 were the United States ( 423 million), the United Arab Emirates 21 million. The United States and the European Union received about 11 million. The Ukrainian government has invested 8 million in the development of startup projects USA. Thus, the development of creative ideas and the formation of startup ecosystems in Ukraine is an important and promising area of ​​economic development, although it is at an early stage. When a creative idea is born on the already formed request of society, there is a high probability of successful launch of a spatrap project. Also, in order to be successful in the market, a startup idea must be characterized by speed of implementation, scalability of the idea, have a quality creative idea, meet the concept of "creative for society", have a small team of like-minded people, cooperate, be open and talk about their ideas.